Making sense of Paul a basic ontroduction to Pauline theology - Wiles, Virginia, 1954- (Peabody, MA Hendrickson, 2000)
Includes bibliographical references and index.
Keywords: Bible. N.T. Epistles of Paul -- theology; Paul, the Apostle, Saint